Precoding Based Interference Suppression for Heterogeneous Multi-Tiered Network - Pinyi Ren; Qinghe Du; Pinyi Sun; Datong Xu (Dianxin kexue)
The coexistence of conventional marcro cells and lowpower small cells form the heterogeneous multi-tiered networks, which can significantly improve the capacity of wireless communications systems. However, the interferences between the marco cells and small cells due to sharing the same frequency band severely degrade the quality of communications and prevent the system capacity from being further enhanced. With the wide application of multiple-input-multiple-output（MIMO）for the 4th generation（4G）mobile communications systems, the interference suppression techniques using MIMO precoding and spatially fading properties have become an attracting and popular research area. The recent progress in the areas of MIMO precoding based interference suppression was introduced. Using the two tier downlink networks as the typical example scenario, the heterogeneous interference model was analyzed and that the key task for interference suppression which pointed out was to jointly design the precoding matrices at transmitters and the processing matrices at receivers and to solve for them in a successive order. Following this principle, several recently emerged MIMO-precoding schemes were further introduced. Finally, the future research direction for interference suppression over heterogenous multi-tiered networks was discussed.